Is kidney function associated with primary open-angle glaucoma?: findings from the Asian Eye Epidemiology Consortium - Tham, Yih-Chung; Tao, Yijin; Zhang, Liang; Rim, Tyler Hyungtaek; Thakur, Sahil; Lim, Zhi Wei; Chee, Miao Li; Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Wang, Ningli; Cao, Kai; Hao, Jie; et al. (British journal of ophthalmology, 2020)
Aim To comprehensively examine the association between kidney function and primary open angle glaucoma (POAG) in a large consortium of multiple Asian population-based studies. - Methods 28 925 participants (57 340 eyes) from 9 population-based studies (from China, Hong Kong, India, Korea, Russia, Singapore) of the Asian Eye Epidemiology Consortium were included. Across all studies, POAG was defined based on the International Society of Geographical and Epidemiological Ophthalmology criteria. Estimated glomerular filtration rate (eGFR) was calculated from serum creatinine. Chronic kidney disease (CKD) was defined as eGFR<60 mL/min/1.73 m2. Eye-specific data were pooled from each study. Multivariable regression analysis with generalised estimating equation models was performed to evaluate the associations between kidney function with POAG and intraocular pressure (IOP). - Results After adjusting for age, gender, study group, hypertension, diabetes, hyperlipidaemia, body mass index, smoking status and IOP, lower eGFR (per 10 mL/min/1.73 m2 decrease) was not significantly associated with POAG (OR=1.01; p=0.77). Presence of CKD was also not significantly associated with POAG (OR=1.01; p=0.739). Furthermore, lower eGFR and presence of CKD were not associated with IOP (all p≥0.12), However, in the subgroup of combined Korean and Chinese individuals, significant associations between lower eGFR (OR=1.09; 95% CI 1.00 to 1.18; p=0.048) and severe kidney function decline (<45 mL/min/1.73 m2; OR=2.57; 95% CI 1.34 to 4.93; p=0.004) with POAG, were observed. - Conclusion In this large pooled-analysis of multiple Asian population-based studies, our findings suggest that the association between CKD and POAG may only be present in East Asians specifically but not in the overall Asian population. Further evaluation in Japanese population is warranted to confirm this observation.